2014
DOI: 10.1103/physrevd.89.025012
|View full text |Cite
|
Sign up to set email alerts
|

Baryonic sphere: A spherical domain wall carrying baryon number

Abstract: We construct a spherical domain wall which has baryon charge distributed on a sphere of finite radius in a Skyrme model with a sixth order derivative term and a modified mass term. Its distribution of energy density likewise takes the form of a sphere. In order to localize the domain wall at a finite radius we need a negative coefficient in front of the Skyrme term and a positive coefficient of the sixth order derivative term to stabilize the soliton. Increasing the pion mass pronounces the shell-like structur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Together with the previous results of Ref. [27], we find two possible incarnations of Skyrmions; one corresponds to a Skyrmion as a spherical domain wall with the S 2 moduli twisted along the S 2 world volume [28], while the other corresponds to a closed vortex string with the U(1) modulus twisted along the S 1 world volume, as illustrated in Figs. 1(c) and 1(d).…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Together with the previous results of Ref. [27], we find two possible incarnations of Skyrmions; one corresponds to a Skyrmion as a spherical domain wall with the S 2 moduli twisted along the S 2 world volume [28], while the other corresponds to a closed vortex string with the U(1) modulus twisted along the S 1 world volume, as illustrated in Figs. 1(c) and 1(d).…”
Section: Introductionsupporting
confidence: 84%
“…the baryon number. It was already found that Skyrmions become baby Skyrmions or lumps when trapped inside a non-Abelian domain wall [25][26][27], and a spherical domain wall with twisted S 2 moduli is a Skyrmion [28], both corresponding to entry (b) in Table I (this relation was generalized to N-dimensional Skyrmions becoming N − 1dimensional Skyrmions inside non-Abelian domain walls in Ref. [26]).…”
Section: Introductionmentioning
confidence: 90%
“…[20], which is possible by changing the sign of the Skyrme term and augment the theory by a sextic derivative term; in this case the domain line with sine-Gordon kinks can still exist.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Unboundedness in every other sector follows from an obvious gluing construction. This point was also missed in a recent paper by Gudnason and Nitta which, likewise, studies skyrmions with c 4 < 0 [17].) In [10] a similar analysis is performed, the potential having been tweaked to produce BPS skyrmions with non-shell-like baryon density.…”
Section: Introductionmentioning
confidence: 99%